Causal associations of Helicobacter pylori infection and metabolic syndrome: insights from a two-sample Mendelian randomization study - Hongwei Wang; Fangying Tian; Caizheng Yang; Xinyu Cui; Yongxia Ding; Ming Zhao; Xueyu Wang; Shanshan Ge (Diabetology & Metabolic Syndrome)
Abstract Background Helicobacter pylori (Hp) infection and metabolic syndrome (MetS) have a high prevalence of co-morbidities and both pose a significant threat to human health and survival. It has been suggested that Hp infection affects the development of MetS in the host, but the causal relationship between the two has not been confirmed. Methods We conducted a two-sample Mendelian randomization study to investigate the causal effect of Hp infection with MetS and its components. Summary statistics for exposure factors (Hp infection) were obtained from the GWAS Catalog (anti-Hp IgG, n = 8,735; Hp VacA antibody levels, n = 1,571; Hp GroEL antibody levels, n = 2,716; Hp OMP antibody levels, n = 2,640). Summary statistics for outcome factors (MetS) were obtained from the most comprehensive genome-wide association study (GWAS) currently available (n = 291,107) as well as from the components of MetS: fasting glucose (n = 46,186), hypertension (n = 461,880), serum triglycerides (n = 115,082), waist circumference (n = 21,949), and high-density lipoprotein (n = 400, 754). The inverse-variance weighted (IVW) method was used as the primary MR method and the robustness of the results was assessed through sensitivity analyses. Results MR analysis showed that anti-Hp IgG levels were positively correlated with waist circumference (β = 0.08, P = 0.012), and GroEL antibody levels showed an opposite correlation with HDL levels (β= -0.03, P = 0.025) and TG (β = 0.02, P = 0.045). In contrast, OMP antibodies levels were positively correlated with both HDL and FBG (β = 0.064, P = 0.037 and β = 0.09, P = 0.003). In the estimation of IVW as the main causal method, VacA antibody level was positively associated with hypertension level and negatively associated with TG (β = 0.02, P = 0.008 and β= -0.02, P = 0.007). Meanwhile, the results of sensitivity analyses showed no heterogeneity or significant level pleiotropy. Conclusions Our study suggests that there is a causal effect between Hp infection and Mets diagnosis and its composition, and further studies are needed to understand the mechanism of its influence.